Transcanal Endoscopic Antrostomy Hole : Its Utility in Restoring Ventilation Pathway to Epitympanum and Mastoid Antrum During Tympanoplasty - Kamal, Sheikh Shawkat (Bangladesh Journal of Endosurgery, 2014)
Aim: To evaluate the role of newly created transcanal endoscopic antrostomy hole as a passage in restoring the aeration of epitympanum and mastoid antrum. Materials & Methods: Study design: Retrospective case series study. Study duration: From January 2013 to January 2014. Study place: Private tertiary care hospital. Patients: 27 ears of 23 adult patients (age ranging from 15years to 54years) underwent transcanal endoscopic tympanoplasty for their chronic middle ear diseases in presence of inflamed middle ear mucosa along with radiological shadows of stagnant fluid in their epitympanum and mastoid antrum. Structured three months follow-up was ensured in every case. Intervention: A hole was created at a selected site of posterior meatal wall purely through transcanal endoscopic approach that established direct communication between mastoid antrum and external auditory canal. Thereafter this newly created passage was used for three purposes- assessment of the condition of mastoid antrum, performing the water test for checking epitympanic patency and in few cases placement of temporary tube for postoperative ventilation and drainage of middle ear. Main out come measures: The feasibility, performance and management of transcanal endoscopic antrostomy hole as passage for reestablishing the aeration of epitympanum and mastoid antrum. Results: The chosen site for antrostomy hole was found effective and safe in providing convenient entrance into the mastoid antrum in every case in this study with out facing technical complexity and failure. Postoperative healing of skin over antrostomy hole was found complete in all ears without any inward growth of skin in to mastoid antrum. Available post operative CT scan imaging of temporal bones showed improved aeration in their epitympanum and mastoid antrum. Conclusions: The role of transcanal antrostomy hole has been proved worthy in restoring ventilation pathway to epitympanum and mastoid antrum during tympanoplasty. This antrostomy hole has the potentiality to be considered in future for placement of long term mastoid ventilation tube in order to treat persistent atelectatic middle ear.